Conamomum vietnamense (Zingiberaceae), a new species from Tay Nguyen, Vietnam - Ly, Ngoc-Sam; Hoang, Thanh-Son; Insisiengmay, Oudomphone; Haevermans, Thomas; Newman, Mark F. (Phytotaxa, 2022)
Conamomum vietnamense, a new species of Zingiberaceae, is described and illustrated from Tay Nguyen (Central Highlands), Vietnam. It is most similar to C. odorum and C. rubidum, but differs in having well-developed stilt roots, elliptic leaf blades, narrowly ovate bracts, abaxially pubescent bracteoles, longer calyx with 2 truncate lobes, broadly obovate to orbicular glabrous labellum, longer filament and glabrous style. Data on distribution, habitat, vernacular name, conservation status and a colour plate of the new species, along with a key to distinguish the species of Conamomum in Cambodia and Vietnam are given.